The Study of Abstract Translation of Non-English Department Student at UPY - Mukmilatul Khasanah Hisyam; Sujatmiko Sujatmiko (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
his study aims (1) to describe the problems of students when they have to translate an abstract from Indonesia to English, (2) to describe translation technique (TT) used by students when translating abstract, (3) to describe the impact of the application of TT used on the quality of abstract translation, (4) to describe the solution that the researcher takes to solve the problems in translating abstract. This study was conducted at University of PGRI Yogyakarta, 27th June 2021. It was qualitative study with total 10 respondents using FGD technique. They were 5 males and 5 females (four students of management, three students of history education, two students of civics education, and one student of mathematics education). Interviews and questionnaire in FGD were used to collect the data. The result showed that (1) the respondents have problems in translating abstract such as in choosing article, in understanding the English, in having less vocabulary, in knowing the meaning, in asking someone’s help to translate, in understanding grammar, in translating abstract without any help from their supervisor and in translating abstract using Google translate only. (2) The respondents used pure borrowing and established equivalent techniques. (3) The application of pure borrowing and established equivalent technique have impacted to the translation quality. Their abstract translation quality score C, D and E. (4) The researcher did the small training as the solution to improve their abstract quality.